Remote Chemical Sensing by SERS with Self-Assembly Plasmonic Nanoparticle Arrays on a Fiber - Zhang, Xin; Zhang, Kunyi; von Bredow, Hasso; Metting, Christopher; Atanasoff, George; Briber, Robert M.; Rabin, Oded (Frontiers in Physics, 2022)
An optical fiber was modified at the tip with a self-assembled plasmonic metamaterial that acts as a miniature surface-enhanced Raman spectroscopy (SERS) substrate. This optical fiber-based device co-localizes the laser probe signal and the chemical analyte at a distance from the spectrometer, and returns the scattered signal to the spectrometer for analysis. Remote SERS chemical detection is possible in liquids and in dried samples. Under laboratory conditions, the analyte SERS signal can be separated from the background signal of the fiber itself and the solvent. An enhancement factor greater than 20,000 is achieved with a monolayer of the SERS marker 4-aminothiophenol.